STATISTICAL STUDY OF PUBLIC HEALTH DISASTER DUE TO ROAD TRAFFIC ACCIDENTS IN INDIA - Patil, Pitambar (International Journal of Research -GRANTHAALAYAH, 2023)
This research article studies the general trend of traffic accidents on Indian roads for the last 28 years. The study includes accident severity, number of deaths, and injuries due to accidents. The rate of accidents, deaths, and injuries are studied concerning population, number of registered vehicles, and road length. Monthly and timely indices are computed for the number of accidents to study which months of a year and time durations of a day show more accidents than its average and with what percentage? We study the general trend of accidents in rural and urban areas and see which categories of vehicles are more vulnerable to accidents in Million Plus Cities. Comments and suggestions are given to minimize road accidents and avoid serious consequences.